Antibacterial Activity of Sea Grape (Caulerpa lentillifera) Methanol Extract against Escherichia coli and Bacillus cereus Bacteria (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTSea grapes are a type of green algae that have not been widely used and are included in seaweed. Seaweed is reported as edible algae, has bioactive substances such as anti-bacterial, anti-fungal, anti-tumor, and can be used to treat high blood pressure and goiter. This study aimed to determine the antibacterial activity of methanolic extract of sea grapes (Caulerpa lentillifera) against Escherichia coli and Bacillus cereus bacteria. The research method for the preparation of sea grapes was by cleaning from all impurities so that sea grapes were free from all impurities, then extracted with 2, 4, and 6% methanol and analyzed descriptively. The test parameters were antibacterial activity and the diameter of the inhibition zone. The results showed that the methanol extract was classified as having antibacterial activity against Escherichia coli and Bacillus cereus bacteria. The concentration of 6% methanol extract had the highest value with an inhibition zone of 2.27% for Escherichia coli and 6.82% for Bacillus cereus. Keywords: Caulerpa lentillifera, Escherichia coli, Bacillus cereus